Characterisation of ion implantation for sub-0.25 micron device manufacturing - Ong, Kok Keng. (2008)
Damage generated by ion implantation have a strong influence on the performance of the silicon substrate and photoresist. This damage was characterised. For photoresist, the damage results in extensive bond breaking of the polymer chain and subsequent release of H2 gas and some volatile hydrogen fragments. The implantation leaves behind a layer of disordered carbon atoms referred to as carbonized layer. This carbonized layer were found to be porous initially but densify upon further bombardments by the ions. Densification was found to proceed in three stages. The initial stage is characterised by C-H bond breaking but little shrinkage leading to the formation of a porous layer. In the intermediate stage, extensive rearrangement of carbon atoms took place resulting in large shrinkage with the porous layer gradually becoming denser as the implantation continues. The final stage kicks in when the entire porous layer is densified with no further observable shrinkage.